School Strategy In Preventing Bullying At SMPN Negeri Arun Lhokseumawe - Nursan Junita; Raudhatul Amimi (Faculty of Medicine University of Malikussaleh, 2022)
Abstract: The purpose of this study is to have a picture of school strategy in preventing bullying at SMP Negeri Arun Lhokseumawe and challenges in apply it. The method that used in this study was a qualitative method with case study type by using purposive sampling techniques. The subject in this study consist of 13 participants, that are 6 teachers, 3 students and 2 parents. The results of this study indicate that strategy that used in preventing bullying behavior at SMP Arun were; (1) Identifying the root of the bullying, (2) Discipline; having the role and consequences,(3) Creating a community of group study or role play, (4) Providing education information about bullying, (5) Providing counselling service for victims and perpetrators by school counselor, (6) giving reward, (7) Do Monitoring, (8) prompting response action from teacher, (9) Build up relationship with parents. However, the obstacles finding in preventing bullying behavior are: (1) Student afraid to repot the case to the teacher, (2) Inconsistency and low of commitment of teacher in applying the role, (4) Communication problem between school and parent. As conclusion the commitment and consistency in applying the role of school strategy is very crucial to prevent bullying at school. The strategic become effective when the role applies comprehensively. Purpose: Describe the school strategy in preventing bullying and challenges of school in applying the role strategy in Arun State Middle School, Lhokseumawe Patients and methods: teachers, parents and students of bullying victims and bullies. Results: The results of this study indicate that strategy that used in preventing bullying behavior at SMP Arun were; (1) Identifying the root of the bullying, (2) Discipline; having the role and consequences,(3) Creating a community of group study or role play, (4) Providing education information about bullying, (5) Providing counselling service for victims and perpetrators by school counselor, (6) giving reward, (7) Do Monitoring, (8) prompting response action from teacher, (9) Build up relationship with parents Conclusion: SMP Arun has applied the strategy to prevent bullying at school. However, to executes the strategy become effective, the commitment and consistency of school is important to ensure the role applied. Furthermore, build up a good communication between school and parents as well as teach student to become assertive will help to prevent cases of bullying.